Comparing health indicators at the city level – the example of Vienna (Italian Journal of Public Health, 2004)
Background. Various projects have identified the need for common indicators for comparing countries andmore recently, regions. The Vienna publication aims to contribute to this discussion.Methods and Results. While not perfect, aggregate measures such as life expectancy and mortality can actas indicators of the general level of health in international comparisons. They are relatively reliable andeasily accessible and are often available at regional levels.Conclusion. Despite their limitations, international reference values provide relevant information on theposition of a country or city within Europe. They can provide inspiration and motivation for policy makers andvisualise past successes
Keywords: health indicator*; compare* (comparing/comparability); regional cit* (city/cities)